Digital information literacy skills and use of electronic resources by humanities graduate students at Kenneth Dike Library, University of Ibadan, Nigeria (2023)
Purpose – The purpose of this paper is to assess the level of digital information literacy (DIL) skill and use of electronic resources by humanities graduate students at Kenneth Dike Library, University of Ibadan, Nigeria. Design/methodology/approach – This paper uses the survey research design and 200 graduate students from the 12 departments that made up the Faculty of Arts in the University of Ibadan participated in the study. A self-devised structured questionnaire was used as instrument for data collection. A pilot questionnaire was first sent to a small random sample of the respondents, with feedback used to fine-tune the final questionnaire. Respondents were requested to rate their level of proficiency in the use of digital devices, web-based tasks, information finding, evaluation and utilisation of available e-resources and challenges encountered. Ethical consideration of informed consent, institutional permission, confidentiality and anonymity of participants was strictly followed. Data collected were analysed and result presented using descriptive statistics including frequencies, percentage, mean and inferential statistics such as regression analysis and Pearson’s product moment correlation coefficient were used to test the research question and hypothesis, respectively. Findings – Humanities graduate students at the University of Ibadan possessed high level of DIL skills in respect of digital devices usage, web-based tasks, information finding and evaluation, but low in e-resources utilisation. This study identified inadequate knowledge of e-resources availability, irregular internet access, inadequate training on e-resources utilisation, inadequate staff assistance, lack of continuity in e-resources subscription and paucity of local contents in the e-resources as main challenges encountered by graduate students in the use of e-resources. To ensure that those who can most benefit from e-resources utilisation are not further marginalised, this study recommends that active steps should be taken to increase e-resources awareness, regular internet access, training/support, continuity of e-resources subscription and increased local content so that all may benefit from the opportunities of the information age. Originality/value – This paper has demonstrated that DIL skills can enhance effective utilisation of eresources if users have adequate knowledge of e-resources availability, regular internet access, adequate training and assistance on e-resources utilisation, continuity in database subscription and adequate local contents e-resources.